PELATIHAN PEMANFAATAN DIGITAL PARENTING CONTROL MENGGUNAKAN GOOGLE FAMILY LINK PADA IBU TAMAN KAMPUNG TANGGUH - Kahfi, Ahmad Hafidzul; Nugraha, Fitra Septia; Ridwansyah, Ridwansyah; Nawawi, Hendri Mahmud (LPPM Universitas Nusa Mandiri, 2024)
The use of digital technology is increasingly widespread in the modern era, which is changing the way parents educate their children.